Consciousness in Post-Modern Times. On Modes of Self-Reflection in Contemporary English Fiction (KULT_online, 2015)
This Bright Inward Cinema of Thought: Stream of consciousness in Contemporary English Fiction by Sara Strauß offers representative cases for the state of the literature techniques used within contemporary English fiction. Divided into six sections, the book presents a panorama of the different narratological modes in the modern era. Beginning with an introduction that considers the theoretical framework, the author shows the development of those modes by reflecting upon aspects of consciousness, such as free indirect style and interior monologue. The book concludes by highlighting the modernist question about consciousness and its reflection on the post-modernism era.